Leptogenys pujoli, a new amazonian species, and the redescription of Leptogenys famelica Emery, 1896 (Formicidae: Ponerinae) - Joshua Pablo Cavalcanti; John Edwin Lattke (Revista Brasileira de Entomologia, 2024)
ABSTRACT We provide an update on the famelica species group, redescribing Leptogenys famelica Emery, 1896 and describing a new species, Leptogenys pujoli n. sp., based on worker specimens. The new species is smaller than L. famelica and can be distinguished by the indistinct mesometanotal suture, and the petiolar node with an anterodorsal margin mostly straight anterior to spiracle in lateral view. Leptogenys famelica is distributed from Costa Rica to Panama, while L. pujoli n. sp. is distributed throughout the Brazilian Amazon, from French Guiana to Bolivia. Some records previously attributed to L. famelica remain uncertain, potentially being either L. famelica or L. pujoli n. sp., or perhaps representing one or more undescribed species. We update the key to Leptogenys workers by Lattke (2011) and include images. We synthesize available knowledge about the possible biology of these species and propose that both L. famelica and L. pujoli n. sp. are generalist predators and that their reproduction is dependent on gamergates.